1994
DOI: 10.1037/0022-0663.86.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Role of parental motivational practices in children's academic intrinsic motivation and achievement.

Abstract: and the families participating in the Fullerton Longitudinal Study for help in various aspects of this study. Thanks are also extended to the reviewers for their valuable suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
171
0
14

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 26 publications
7
171
0
14
Order By: Relevance
“…Six items developed for the Bridges RCT (e.g., I asked my child what he/she did at school) and four items adapted from Gottfried, Fleming and Gottfried's (1994) Extrinsic Motivation subscale of the Parent Motivational Practices Scale (e.g., "I helped my child get involved with extra programs or classes") assessed FCG involvement in child's education. The items represented intervention-targeted parenting practices (e.g., emphasis on school attendance and performance); FCGs reported if they had done each practice (0 = no, 1 = yes) in the past month (α = 0.68).…”
Section: Parent Perceptions Of Participation Benefitsmentioning
confidence: 99%
“…Six items developed for the Bridges RCT (e.g., I asked my child what he/she did at school) and four items adapted from Gottfried, Fleming and Gottfried's (1994) Extrinsic Motivation subscale of the Parent Motivational Practices Scale (e.g., "I helped my child get involved with extra programs or classes") assessed FCG involvement in child's education. The items represented intervention-targeted parenting practices (e.g., emphasis on school attendance and performance); FCGs reported if they had done each practice (0 = no, 1 = yes) in the past month (α = 0.68).…”
Section: Parent Perceptions Of Participation Benefitsmentioning
confidence: 99%
“…Such effects have been explained as depending on the extent to which the recipient of external consequences perceives being controlled by the contingency, with greater control associated with lower motivation (Deci & Ryan, 1992; A. E. Gottfried, 198613). Regarding academic intrinsic motivation, in a longitudinal study of parental motivational practices, A. E. Gottfried, Fleming, et al (1994) found that children had Significantly lower academic intrinsic motivation with greater parental use of task extrinsic motivational practices, whereas children had significantly higher academic intrinsic motivation with greater parental use of task endogenous motivational practices (i.e., encouraging children's intrinsic motivation).The role of the caregiver in infants' and preschoolers' mastery motivation has also been studied. Caregiver activities that are positively related to manifestations of mastery motivation (e.g., persistence, goal directedness of behavior, and problem solving) have been shown to include variety of cognitively oriented caregiver activities, variety of the inanimate environment, contingent responsivity of the caregiver to the child, responsivity and challenge level of toys and stimuli, and parents' kinesthetic, tactile, and auditory stimulation (Busch-Rossnagel, Knauf-Jensen, & DesRosiers, 1995;Wachs, 1987;Yarrow et al, 1984;Yarrow, Rubenstein, & Pedersen, 1975).…”
mentioning
confidence: 99%
“…The models tested in phase 1 consisted of the home environment factor (age 8 years) and academic intrinsic motivation (ages 9/10, and 13 years). Phase 2 models included home environment and socieconomic status (age 8 years), and academic intrinsic motivation (age 9, 10, and 13 years).Based on past research indicating the greater specificity of the math subscale of the CAIMI, and the greater uniqueness of math as a subject area in academic intrinsic motivation (A. E. Gottfried, , 1990A. E. Gottfried, Fleming, et al, 1994), two different models were evaluated in both phase 1 and phase 2 analyses.…”
mentioning
confidence: 99%
“…De nombreuses recherches ont effectivement montré que les résultats scolaires d'un étudiant sont d'autant meilleurs qu'il est intrinsèquement motivé (Flink, Boggiano, Main, Barrett et Katz, 1992 ;Fortier et al, 1995 ;Gottfried, 1985Gottfried, , 1990Gottfried, Fleming et Gottfried, 1994 ;Grolnick et al, 1991 ;Guiffrida, Lynch, Wall et Abel, 2013 ;Kaufman, Agars et Lopez-Wagner, 2008 ;Komarraju, Karau et Schmeck, 2009 ;Miserandino, 1996). Deux études menées par montrent, par exemple, que des activités scolaires réalisées par choix ou par plaisir garantissent de meilleurs résultats que des activités engagées pour des raisons instrumentales ou sous l'effet de pressions intériorisées ; ce résultat se vérifie également en contrôlant l'effet de la performance scolaire anté-rieure.…”
Section: La Théorie De L'autodéterminationunclassified